The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.14393/hygeia1332351
|View full text |Cite
|
Sign up to set email alerts
|

Catadores De Materiais Recicláveis: Perfil Social E Riscos À Saúde Associados Ao Trabalho

Abstract: O modelo de desenvolvimento econômico vigente e os hábitos de consumo da população estão entre os fatores que tem levado muitas pessoas à ocupação como catadores de material reciclável. Esse trabalho teve como objetivo conhecer o perfil sócio demográfico dos catadores na cidade de Chapecó, SC e analisar os riscos à saúde dos trabalhadores associados ao ambiente de trabalho. Foram entrevistados catadores residentes e atuantes na cidade, no período entre abril e junho de 2015. Foram entrevistados ao todo 39 cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(7 reference statements)
1
0
0
1
Order By: Relevance
“…In the present study, most cooperative members were female and married, consistent with the studies by Lutinski et al 13 and Bonini-Rocha et al 14 In this sense, this professional activity is considered as a strategy of social inclusion for this part of the population, who lives in vulnerable conditions. 13 With regard to schooling, a study by Conceição & Silva 15 showed that low schooling increases the number of informal workers, leading to the hypothesis that they are recyclable waste pickers. In agreement with the present study, several authors report low schooling levels in workers and recyclable waste pickers.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, most cooperative members were female and married, consistent with the studies by Lutinski et al 13 and Bonini-Rocha et al 14 In this sense, this professional activity is considered as a strategy of social inclusion for this part of the population, who lives in vulnerable conditions. 13 With regard to schooling, a study by Conceição & Silva 15 showed that low schooling increases the number of informal workers, leading to the hypothesis that they are recyclable waste pickers. In agreement with the present study, several authors report low schooling levels in workers and recyclable waste pickers.…”
Section: Discussionsupporting
confidence: 92%
“…Neste sentido, a dura realidade é que as pessoas que sobrevivem da coleta, embora sejam os protagonistas do processo de reciclagem, foram marginalizadas e invisibilizadas ao longo dos anos, a ponto de serem consideradas insignificantes (Neves et al, 2017). Por conta disso, além das dificuldades inerentes à profissão, os catadores se deparam com uma série de preconceitos devido à natureza de sua atividade.…”
Section: Fonte: Os Autores (2022)unclassified
“…No caso dos catadores de materiais recicláveis, são visíveis os inúmeros desafios a serem enfrentados, a exemplo de melhores condições de trabalho, desenvolvimento de políticas públicas no sentido de estabelecer estratégias de desenvolvimento social e econômico, e o fortalecimento das associações para ampliar a organização do trabalho de forma cooperativa. 24 Neste estudo evidenciou-se que um desafio importante enfrentado por esses trabalhadores está relacionado às condições de vida, de trabalho e de acesso aos serviços de saúde.…”
Section: (E10 62 Anos)unclassified